Innovation planning - Nazif, Emine (Vilnius University Open Series, 2019)
The report examines theoretical assumptions regarding the nature and importance of innovation. Regardless of the diversity we see in terms of defining different types of innovation, we can come to the conclusion that all definitions have one common feature and it relates to focusing on the presence of something new and different. Innovation planning processes are discussed by indicating that they are aimed at defining specific actions so that the objectives set out in the company’s innovation strategy can be achieved. The most important functions of planning are to coordinate the efforts of the participants in the innovation process and to link business objectives and opportunities for future development. Emphasis is placed on the importance of innovation for each organization and the necessary investment of efforts for appropriate innovation planning that provides competitive advantages.